Pengaruh Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Melalui Motivasi Kerja Pada PT. Bank Central Asia Cab. Harapan Indah - Kristian Kindo; Bungaran Saing (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study investigates the influence of the work environment and work discipline on employee performance, with work motivation serving as a mediating variable at the Harapan Indah Branch of PT Bank Central Asia Tbk. A quantitative research design was adopted, and all statistical analyses including validity, reliability, normality, multicollinearity, and heteroscedasticity testing, multiple linear regression, independent t-tests, the F-test, the Sobel test, and calculation of the coefficient of determination were performed using IBM SPSS Statistics 26. The results demonstrate that both the work environment and work discipline exert a positive and statistically significant effect on work motivation. Similarly, these two factors also have a positive and significant direct impact on employee performance. Work motivation itself is also found to have a positive and significant effect on performance. Collectively, the three variables explain a substantial portion of variance in employee performance, with an adjusted coefficient of determination (Adjusted R²) of 0.688 (68.8%), indicating strong explanatory power. The Sobel test further verifies that work motivation significantly mediates the relationship between the work environment and employee performance, as well as the relationship between work discipline and employee performance. Overall, the findings underscore that fostering a supportive work environment, upholding consistent work discipline, and enhancing employee motivation are essential strategies for optimizing employee performance in this organizational setting.